The RNA polymerase of influenza a virus: mechanisms of viral transcription and replication. - Fodor, E (2013)
The influenza A virus RNA genome segments are packaged in ribonucleoprotein complexes containing RNA polymerase and nucleoprotein. The ribonucleoprotein is involved in the transcription of viral genes and replication of the viral RNA genome in the nucleus of the infected cells, and represents the minimal transcriptional and replicative machinery of an influenza virus. During transcription, the viral RNA polymerase synthesizes capped and polyadenylated mRNA using 5΄ capped RNA primers. During replication, the viral RNA polymerase generates a complementary RNA (cRNA) replication intermediate, a full-length complement of the vRNA that serves as a template for the synthesis of new copies of vRNA. The nucleoprotein is also an essential component of the viral transcriptional machinery. The molecular determinants of the transcriptional and replicative activities of the viral RNA polymerase are not fully understood, but recent data suggest that transcription is performed by a cis-acting RNA polymerase, forming part of the ribonucleoprotein complex, while replication might be carried out by a trans-acting RNA polymerase. Viral as well as cellular factors are known to be involved in the regulation of the activities of the RNA polymerase, e.g. the viral nuclear export protein has been shown to regulate the accumulation of viral transcription and replication products. The viral transcriptional machinery represents an attractive target for the development of antiviral drugs and lead compounds targeting nucleoprotein and the PA endonuclease domain of the RNA polymerase have already been identified.